Which is the real Plesiopelma longisternale? (Araneae: Theraphosidae) revision of types, molecular phylogeny and morphology - Ferretti, Nelson Edgardo (2023)
Plesiopelma longisternale (Schiapelli & Gerschman, 1942) is a medium-sized tarantula widely distributed in Argentina and Uruguay. This species is very common in northern and central Argentina inhabiting mountainous systems and open areas where it construct shelters covered with dense silk. There are some degree of morphological variation among populations from different areas, mainly in the body size and male palpal bulb and such variation may even found in a single locality. Moreover, the holotype male and allotype female are described from different localities. The aim of this work is to examine and re-describe the types of P. longisternale and construct a dataset of cytochrome c oxidase subunit I (COI) sequence to asses species limits within P. longisternale. We obtained sequences from most populations of northern and central Argentina and present the results of a species delimitation analysis using ABGD, mPTP and GYMC. The resulting molecular species delimitation and morphology unveils a new species of Plesiopelma and corroborate the identity of Plesiopelma longisternale. In addition, from the examination of types, we noticed that the genitalic features drawn in the original publication of the holotype male are not congruent with the specimens deposited.